Perbandingan Hasil Belajar Menggunakan Model Picture and Picture dengan Examples Non Examples Pada Pembelajaran PKn - Nurul Lifa Rahmawati; Osa Juarsa; Abdul Muktadir (Universitas Bengkulu, 2023)
This research aims to analyzed comparison the outcomes cognitif learning use Picture And Picture learning model with Examples Non Examples learning model. This type of research is a quantitative research. The research design used was Quasi Experimental Design with design type The Matching Pretest-Posttest Comparison Group Design. The test is done twice before and after giving treatment (treatment) in the class. The subjeck in this study is divided into two groups: students of class IV A in SDN 76 Kota Bengkulu as a experimental group 1 and students of class IV B at SDN 76 Kota Bengkulu as experimental group 2. The research instrument used is a learning result test with multiple choice questions given through pretest before the learning takes place and posttest after the learning takes place. Data of this research are analyzed by using descriptive analysis and inferential analysis that is t-test (independent sample t-test). Data of research result which is processed by using t test obtained t hitung equal to 2,34 and ttabel value equal to 1,667. Systematically seen thitung 2,34 > ttabel 1.667 at 5% significant level, This shows that there are differences in learning outcomes between students taught by using pictures and pictures learning model with examples non examples learning model. then the average of the result study of Picture and Picture learning model was (68,22) and Example Non Example was (58,03).The concluded that the Picture and Picture learning model more effective to highest students result study.